2020
DOI: 10.1080/23322039.2020.1750259
|View full text |Cite
|
Sign up to set email alerts
|

Corporate growth strategies and financial performance of quoted manufacturing firms in Nigeria: The mediating role of global economic crises

Abstract: This study examines the mediating role of global economic crises (GECs) in the effect of growth strategies on Nigerian manufacturing firms' performance. The study used secondary data for the period between 2000 and 2017 in its analysis. Therefore, an expost facto research design was used in the analysis of 120 firms listed on the Nigerian Stock Exchange, which were selected out of 190 listed firms using a judgmental sampling technique. The researchers follow data cluster analysis approach to analyze the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, this study affirms the result of the study conducted by Musi et al (2018) that business strategies positively and significantly affect firm profitability. In another study, by Abolarinwa et al (2020) the result further established the fact that business strategies have a positive effect on firm profitability. Ndambuki et al (2017) similarly asserts that the relationship between business strategies and firm profitability is significantly positive.…”
Section: Discussion Of Findingsmentioning
confidence: 81%
“…Furthermore, this study affirms the result of the study conducted by Musi et al (2018) that business strategies positively and significantly affect firm profitability. In another study, by Abolarinwa et al (2020) the result further established the fact that business strategies have a positive effect on firm profitability. Ndambuki et al (2017) similarly asserts that the relationship between business strategies and firm profitability is significantly positive.…”
Section: Discussion Of Findingsmentioning
confidence: 81%
“…In this regard, Dimova and Pela (2018) support that a wise and careful selection of resources and their allocation leads to healthy financial status in businesses. Abolarinwa et al (2020) also found that firms that were effective in formulating and implementing strategies were early adopters of disruptive technologies, leading to superior performance. Other researchers (Cheng et al, 2014;Yusuf et al, 2012;Luo et al, 2015;Bodnar et al, 2018) found that effective strategy implementation leads to numerous desirable outcomes in areas such as stakeholder management, corporate social responsibility, supplier management, and asset utilisation.…”
Section: The Effects Of Strategy Implementation On Financial Performa...mentioning
confidence: 97%
“…Rajendra, (2008) mentions that FP management is an integral part of the business management field and is also crucial for the survival of businesses. Superior FP is linked to outcomes such as excellent stakeholder relationships, improved technology adoption, competitive advantages, more significant market share and greater economies of scale (Abolarinwa et al, 2020). In light of this, SMEs must adopt prudent financial management practices to ensure their ultimate prosperity and survival (Ferreira, 2007).…”
Section: Financial Performance and The Survival Of Smesmentioning
confidence: 99%
“…In summary, many approaches and techniques for business expansion might result in the growth of several divisions and areas. It is the reality that this pattern becomes very important in utilizing the advantage, lowering manufacturing costs, and boosting profitability in businesses as firm scale develops to a certain degree (Abolarinwa et al, 2020).…”
Section: Growth Strategymentioning
confidence: 99%